KEBIJAKAN PEMERINTAH DAERAH KOTA PEKANBARU DALAM PENGELOLAAN SAMPAH DENGAN KONSEP 3R TAHUN 2017 - Ramadhan, Dilva; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The title of this research is Government Policy in Waste Management with the 3R Concept in Pekanbaru in 2017. The dynamics of the development of the city of Pekanbaru which is quite rapid and accompanied by rapid population growth has brought consequences on increasing the volume of waste by the community. society, included in the category of complex cleaning problems. This means that it needs a fast, precise, careful, advanced and directed handler from the regional government through related policies. Based on Pekanbaru City Regulation No 08 of 2014 concerning waste management. It is mandated that cleanliness management is the responsibility of the local government, in this case carried out by the Pekanbaru City Environment and Hygiene Office (DLHK). In this study the authors used qualitative. Jhon W. Creswell (2010) who explained that qualitative research are methods of exploring and understanding meaning by a number of individuals and groups of people ascribed to social or humanitarian problems. In this research the writer tries to explain the description of government policy in waste management with the 3R concept and the factors that influence government policy in waste management with the 3R concept in Pekanbaru City. The results of this study concluded that the waste management process with the 3R concept was needed through several stages, first, the government conducted socialization to the community carried out by the Pekanbaru environment and cleanliness department in reducing waste with the 3R concept. The second stage socializes how to use waste that is still in use and recycles waste that can be recycled, so that it has a sale value.Â Keywords: Restrictions on the Use of Waste, Reuse, Waste Recycling.Â